Modernism at the beach : queer ecologies and the coastal commons - Freed-Thall, Hannah (Modernist latitudes., 2023)
"At the beach, bodies converge with the elements and strange treasures come to light. Departing from the conventional association of modernism with the city, this book makes a case for the coastal zone as a surprisingly generative setting for twentieth-century literature and art. An unruly and elusive confluence of human and more-than-human forces, the seashore is also a space of performance—a stage for loosely scripted, improvisatory forms of embodiment and togetherness. The beach, Hannah Freed-Thall argues, was to the modernist imagination what mountains were to Romanticism: a space not merely of anthropogenic conquest but of vital elemental and creaturely connection. With an eye to the peripheries of capitalist leisure, Freed-Thall recasts familiar seaside practices—including tide-pooling, beachcombing, gambling, and sunbathing—as radical experiments in perception and sociability. Close readings of works by Marcel Proust, Virginia Woolf, Claude McKay, Samuel Beckett, Rachel Carson, and Gordon Matta-Clark, among others, explore the modernist beach as a queer refuge, a precarious commons, a scene of collective exhaustion and endurance, and a visionary threshold at the end of the world. Interweaving environmental humanities, queer and feminist theory, and cultural history, Modernism at the Beach offers new ways of understanding twentieth-century literature and its relation to ecological thought."--